Synthesis of Some New 3-(Substituted phenyl)-5-(9-anthryl)-2-pyrazolines, 1-Phenyl-3-(substituted phenyl)-5-(9-anthryl)-2-pyrazolines and 2-(9-Anthryl)-4-(substituted phenyl)-1,5-benzothiazepines as Antibacterial Agents - Dawane, B.S.; Vibhute, Y.B.; Konda, S.G.; Mali, M.R. (Asian Journal of Chemistry, 2010)
The title compounds have been synthesized from the corresponding 1-(substituted phenyl)-3-(9-anthryl)-2-propen-1-one (I) by condensation with hydrazine hydrate, phenyl hydrazine and 2-amino-thiophenol. The structures of the new compounds were established on the basis of analytical and spectral data. All the compounds have been screened for their antibacterial activity.